2021
DOI: 10.3389/fonc.2021.656190
|View full text |Cite
|
Sign up to set email alerts
|

FOXP3 Inhibits the Metastasis of Breast Cancer by Downregulating the Expression of MTA1

Abstract: BackgroundFOXP3, as a tumour suppressor gene, has a vital function in inhibiting the metastasis of breast cancer cells, but the mechanisms by which it inhibits metastasis have not been fully elucidated. This study intended to explore a new mechanism by which FOXP3 inhibits breast cancer metastasis.MethodsBioinformatic analysis was performed to identify potential downstream molecules of FOXP3. The function of FOXP3 in inhibiting MTA1 expression at the mRNA and protein levels was verified by real-time PCR and We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 32 publications
2
13
2
Order By: Relevance
“…Nuclear FOXP3 expression was verified as an independent favorable factor for OS in BRCA, especially in TNBC. This finding is essentially consistent with recent studies (12,13).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Nuclear FOXP3 expression was verified as an independent favorable factor for OS in BRCA, especially in TNBC. This finding is essentially consistent with recent studies (12,13).…”
Section: Discussionsupporting
confidence: 94%
“…This ability of transcriptional regulation may well be the potential superiority of FOXP3 in relative to prior biomarkers of BC. It has been reported that FOXP3 can inhibit the transcription of the proto-oncogene HER2 (10) and the expression of runt-related transcription factor 1 (RUNX1) (11), vascular endothelial growth factor (VEGF) (12), and metastasis-associated 1 (MTA1) (13) to perform its anticancer function in BC. However, the biological function and molecular mechanism of FOXP3 in BC have not been fully illustrated.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical specimen analyses also showed a negative relationship between VEGF and nuclear FOXP3 expression. A similar pathomechanism was found by Liu et al [ 31 ], they revealed that FOXP3 can bind to the MTA1 (metastasis-associated 1) promoter and downregulate the transcriptional activity of the MTA1 gene. MTA1 influences local invasion and lymph-node metastasis and regulates downstream gene transcription activity.…”
Section: Foxp3’s Effects On Tumor Metastasissupporting
confidence: 80%
“…For example, FOXP3 can directly bind to the promoter of CD44 and inhibit its protein expression, thereby inhibiting the adhesion, invasion and metastasis of human breast cancer cells [49]. In addition, FOXP3 can downregulate the expression of Metastasis-associated 1 (MTA1) in breast cancer cells by directly inhibiting the activity of the MTA1 promoter, affecting the ability of breast cancer cells to invade and metastasize in vitro and in vivo [50].…”
Section: Tumour-foxp3 As a Tumour Suppressormentioning
confidence: 99%